Mixed convection of water-based nanofluids in a rectangular inclined lid-driven cavity partially heated from its left side wall - Hussein A.K.; Ahmed S.E.; Mohammed H.A.; Khan W.A. (2023)
This paper examines the thermal and flow fields characteristics of laminar steady mixed convection flow in a rectangular inclined lid-driven cavity filled with water-based nanofluids numerically using finite difference method. Whilst a uniform heat source is located on a part of the left inclined sidewall of the cavity, the right inclined sidewall is considered adiabatic together with the remain parts of the left inclined sidewall. The top and bottom walls are maintained at a relatively low temperature and the top wall moves from left to right with uniform lid-driven velocity. The fluid inside the cavity is a water based nanofluid containing different types of solid spherical nanoparticles: Cu, Ag, Al2O3, and TiO2. Based on the numerical simulation, the effects of the dominant parameters such as Richardson number, cavity inclination angle, solid volume fraction, heat source effect and type of nanoparticles are examined. The numerical results are obtained for inclination angles ranging from 0 to 90, for Reynolds numbers varying from 1 to 100 and for the solid volume fractions varying from 0% to 20%. Comparisons with previously published numerical works on mixed convection in a nanofluid filled cavity are performed and good agreements between the results are observed. It is found that the local Nusselt number is seen to decrease as the inclination angle and solid volume fraction increase. Also, the results of the present study indicate that the presence of nanoparticles in the fluid is found to alter the structure of the fluid flow. Moreover, it is observed that the shape of the circulation vortex is sensitive to the inclination angle and addition of nanofluids. 2013 American Scientific Publishers. All rights reserved.